The position of minorities in the Turkish foreign policy (1923-1974) - Madanoğlu, Deniz (İstanbul Bilgi Üniversitesi, 2007)
Türkiye'deki azınlıkların hakları ve bu hakların idaresi çoğu zaman yoğun tartışmaların, siyasi farklılıkların ve toplumsal yargıların konusu olmuştur. Tüm bu ayırımlara rağmen azınlıklarla ilgili iç ve dış politika tüm dönemler içinde değişmez bir şekilde Cumhuriyet'in ideolojik milli kimlik anlayışına bağlı bir şekilde yürütülmüştür. Bu resmi `Türk milleti' kavramı politikacıların azınlıkları, onların etnik farklılıklarının gerçeklerini de yok sayan, zorlu bir Türkleşme sürecinden geçirmelerine ve bu süreç içinde de azınlıkların dışlanmasına yol açmıştır. Bu programlar azınlıkları ikinci sınıf vatandaş olarak gören ve onları uluslararası arenanın reel-politiği içinde sürekli koz olarak kullanan dış politika uygulamaları ile el ele gitmiştir. Bu tarz dış politikalar azınlık nüfusunun dışlanmasının yanı sıra Türk insanın psikolojisinde de kişisel seviyede bu dışlanmayı benimseyen ve cesaretlendiren bir ulusal kimlik hissi oluşmasında da etkili olmuştur. Varlık Vergisi, Mübadele, 6-7 Eylül Olayları ve Rumların sınırdışı edilmesi gibi olaylar bu süreci işaretleyen tarihsel vakaların kimileri olmuştur, ve toplumsal hafızada silinmez bir yer etmelerine bağlı olarak tarafsız toplumsal analizlere muhtaçtır.

The question of policy with regards to the management of the rights of minorities within Turkey has at certain intervals, as is now, a matter of intense public debate as well as political differences and social grievances. Despite such fervor, both foreign and internal policy regarding the issue of minorites has traditionally been inextricably tied to the Republic?s ideological perception of national identity. This official perception of Turkish nationality has led policy makers to force minorities through a tough Turkification process which disregards the realities of ethnic diversities, as well as and complimenting with the gradual social externalization of these minority groups. These programs have gone hand in hand with foreign policies which perceive the minorities as second rate citizens and have continuously played them as trump cards within the real-political structure of the international arena. Such foreign policy has also been affective in both alienating the minority population and embedding within the psychology of the Turkish people a sense of national self-identity which welcomes and encourages this alienation at the individual level. Practices such as the Capital Tax, Population Exchange, the Events of 6-7th September, and the deportation of Rums are some of the historical events which tragically mark these processes, having become an unerasable part of our social memory in dire need of objective social analysis.
Türkiye'de azınlıkların dış politikadaki yeri (1923-1974)